DIFFERENTIAL LEARNING DESIGN TO OPTIMIZE THE POTENTIAL OF VISUALLY IMPAIRED STUDENTS - Gunawan; Khasanah, Uswatun (Tahta Media Group, 2025)
This study aims to analyze the learning needs of a speech-impaired student, design a differentiated learning model contextualized to the characteristics of the madrasah, and examine the effectiveness of the design in improving student participation and learning achievement. The research employed a Research and Development (R&D) approach conducted at MI Muhammadiyah Klaseman. The research subjects consisted of one fifth-grade speech-impaired student and a classroom teacher as a supporting informant. Data were collected through observation, interviews, documentation, and limited trials. The needs analysis revealed that the primary barrier faced by the student was instructional communication access rather than cognitive ability. The developed differentiated learning model included differentiation of content, process, product, and learning environment through visual supports and alternative non-verbal responses. The effectiveness test showed an improvement in learning participation from low to high category and an increase in learning achievement with an N-gain score of 0.57 (moderate category). The study concludes that a needs-based differentiated learning design is effective in optimizing the potential of speech-impaired students and strengthening the implementation of inclusive education in Islamic elementary schools.